Meigs’ syndrome with elevated CA-125 and HE-4: a case report and literature review - Jichang Seong; Abdusattorov Ravshan; Sametdinov Narkhodzha; Kurbanova Saida; Alimov Jamshid; Alimov Jamshid; Babanov Bahriddin; Sharobidinov Biloliddin (Frontiers in Medicine)
Meigs’ syndrome is a rare gynecological condition characterized by a benign ovarian tumor, ascites, and pleural effusion, all of which resolve spontaneously after tumor removal. While mildly elevated serum CA-125 levels are frequently observed, levels exceeding 1,000 IU/mL are extremely rare, and concurrent elevation of other tumor markers, such as HE-4, may further complicate its diagnosis. We report a case of Meigs’ syndrome in a 41-year-old premenopausal woman. Initial presenting symptoms included severe dyspnea, abdominal distention, anorexia, and weight loss. Subsequent imaging studies revealed a large right ovarian tumor accompanied by massive ascites and pleural effusion. Serum CA-125 and HE-4 levels were markedly elevated (1,200 IU/mL and 82.1 pmol/L, respectively), with a Risk of Ovarian Malignancy Algorithm (ROMA) score of 25.63%, suggesting advanced ovarian malignancy. Neoadjuvant chemotherapy was initiated, but the tumor continued to grow, necessitating internal debulking surgery. Postoperative histopathology revealed a benign ovarian fibroma, confirming the diagnosis of Meigs’ syndrome. Spontaneous resolution of ascites and pleural effusion occurred by the second postoperative day, and the tumor markers normalized within the next six months. The patient remained disease-free at 2-year follow-up. This case underscores the importance of considering Meigs’ syndrome in patients with markedly elevated tumor markers, an ovarian tumor unresponsive to chemotherapy, and concomitant ascites and pleural effusion. Early recognition and surgical intervention are critical for accurate diagnosis and optimal management of this rare condition.